PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2016-2020 - Ajeng Ayu Utari; Wawan Sukmana; Laras Pratiwi (LP2M Universitas Perjuangan Tasikmalaya, 2021)
ABSTRACT Intellectual Capital has a role in the knowledge-based business that companies need. Intellectual Capital is believed to be able to contribute in increasing the value of the company. This study aims to determine the effect of Intellectual Capital on Firm Value in Telecommunication Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The method used in this research is descriptive associative with a quantitative approach. The source of data in this study is secondary data with data collection techniques through library research and documentation. The population in this study are telecommunication sub-sector companies listed on the Indonesia Stock Exchange as many as six companies. The number of samples obtained as many as four companies selected by perposive sampling method. While the analysis technique used is simple regression, correlation coefficient, coefficient of determination and T test using SPSS V.26. The results of the study show that Intellectual Capital has a significant effect on firm value in the Telecommunication Sub-Sector Company for the 2016-2020 period.